Anaerobic Propane Oxidation for Biological Sulphate and Thiosulphate Reductions - Gusti Diansyah (UNIVERSITAS SRIWIJAYA, 2014)
The existence of microbial populations that use short chain alkanes (SCA) (ethane, propane andbutane) as potential electron donors for the reduction of sulphate has been recently reported. The useof sulphur compounds in many chemical processing leads wastewaters containing high concentrationof sulphate and thiosulphate. Batch experiments were studied to determine the ability of mixedsediment cultures from Aarhus and EckernfÃ¶rde Bay to anaerobically reduce sulphate andthiosulphate coupled to propane as electron donor. In the presence of propane, sulphide productionfrom all sulphate and thiosulphate bottles was higher than the sulphide production when thepropane was not added.Keywords: anaerobic oxidation, sulphur compounds, sulphide production